Leg stiffness asymmetry during running in high level female track athletes - Wileman, T.; Moresi, M.; Millet, E. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to assess potential leg stiffness asymmetry in female track athletes during race-paced running. Sixteen high level female athletes from two different event groups (sprints and endurance) completed six to ten 55 m runs. Three-dimensional motion analysis was used to calculate dominant and non-dominant limb leg stiffness measures which were subsequently used to identify potential leg stiffness asymmetry. Results indicated a low-moderate prevalence of leg stiffness asymmetry among endurance runners (29%) however a greater percentage of athletes with leg stiffness asymmetry were identified in the sprints group (66 %). Leg stiffness asymmetries among sprinters may place these athletes at increased injury risk and regular monitoring of athletes for early injury risk identification may be